Inferior vena cava thrombosis as the initial presentation of IgG4-related retroperitoneal fibrosis: Case report and literature review. Issue 3 (October 2018) - Simopoulou, Theodora; Klimopoulos, Serafim; Sampaziotis, Dimitrios; Tzortziotis, Apostolos; Bogdanos, Dimitrios; Sakkas, Lazaros I
IgG4-related disease is an immune-mediated deposition of fibro-inflammatory tissue with IgG4-positive plasma cells and dense fibrosis in a single or multiple organs. It often raises concern for malignancy requiring biopsy for diagnosis. Presentation may vary according to organ involved. IgG4-related retroperitoneal fibrosis accounts for two-thirds of the previously considered idiopathic retroperitoneal fibrosis cases. In IgG4-related retroperitoneal fibrosis, computed tomography scan or magnetic resonance imaging shows periaortic soft tissue that extends from below the kidneys to iliac arteries and entrap ureters causing hydronephrosis and renal failure. We present a rare case of IgG4-related retroperitoneal fibrosis presenting with leg swelling and pain due to inferior vena cava compression and thrombosis, and we review current concepts on disease pathogenesis, diagnosis and treatment.